The Effectiveness of Illustrated Word Cards in Increasing Reading Interest of Children at Al-Jami'atul Amaliyah Gerumpung Kindergarten, Sepit Village, Academic Year 2022/2023 - Syarifatul Munawarah; Ahmad Izzuddin; Yuliana Susanti (Journal of Education, Teaching, and Learning, 2024)
The aim of this research is to determine the effectiveness of illustrated word card media in increasing the reading interest of children at Al-Jam’iyatul Amaliyah Gerumpung Kindergarten in Sepit Village for the Academic Year 2022/2023. The research method used is descriptive qualitative with a survey research design. This study was conducted at Al-Jam‟iyatul Amaliyah Gerumpung Kindergarten in Sepit Village, Keruak Sub-district, East Lombok, West Nusa Tenggara. Three data collection techniques were employed: observation, interviews, and documentation. The data analysis technique used is descriptive analysis with components of data reduction, data presentation, and verification. The research results indicate that illustrated word card media has a positive impact on increasing children's reading interest at Al-Jamiatul Amaliyah Gerumpung Kindergarten in Sepit Village. This is evident from the responses of 5 out of 6 teachers, representing 83.33%, who have a positive outlook. Out of the total 20 participating students, 14 students showed a positive response, accounting for 70%. Additionally, among the 15 parents participating in this study, 12 respondents, or 80%, expressed a positive perspective. Therefore, it can be concluded that illustrated word card media is effective in enhancing the reading interest of children at Al-Jam’iyatul Amaliyah Gerumpung Kindergarten.